Problematic Internet Use in Undergraduate Health Science Students at a Remote Place of Nepal: A Cross-Sectional Study - Jha, Jay Prakash; Pun, Dilli Bahadur; Amgain, Kapil; Chaudhary, Hiramani Prasad (Journal of Karnali Academy of Health Sciences, 2023)
Background: Problematic internet use (PIU) is a growing concern among teenage and college students. Excessive internet use has detrimental effects on physical and mental health. This study aims to assess the computer usage pattern and calculate the frequency of PIU in undergraduate health science students at Karnali Academy of Health Sciences, Jumla, a remote place of Nepal. Methods: A cross-sectional questionnaire-based study was conducted from October to November 2022. Data were collected from all the undergraduate students who consented to participate. The questionnaire included students’ computer-related behaviours. PIU was defined as a score of 42 or above on the PIU questionnaire. Data were analyzed by descriptive and analytical statistics, keeping p value <0.05 as significant. Results: Among 127 students, majority used smartphones and laptops, primarily for social media. The mean duration of internet use was 6.09±2.63 years, with an average daily use of 2.54±2.05 hours on weekdays and 3.88±2.2 hours on weekends. The prevalence of PIU among the participants was 43.3%, which was not significantly different by gender (p=0.094). The PIU score was positively correlated with annual income of family, years of internet use, and daily screen and internet use time (p<0.05). Conclusion: PIU is prevalent among undergraduate health science students at Karnali Academy. The findings emphasize the need for awareness, guidance, and proper planning to promote healthy internet usage habits among students. Educational institutions should play an active role in implementing strategies to address PIU and support students for a healthy internet use.